2022
DOI: 10.3390/ijms232314687
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Cell Markers in Circulating Tumor Cells from Patients with High-Grade Ovarian Serous Carcinoma

Abstract: Cancer is primarily a disease in which late diagnosis is linked to poor prognosis, and unfortunately, detection and management are still challenging. Circulating tumor cells (CTCs) are a potential resource to address this disease. Cell fusion, an event discovered recently in CTCs expressing carcinoma and leukocyte markers, occurs when ≥2 cells become a single entity (hybrid cell) after the merging of their plasma membranes. Cell fusion is still poorly understood despite continuous evaluations in in vitro/in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Beside the importance of physiological cell fusion, there is profound scientific consensus that cell-cell fusion events also occur in human cancers and that disease progression can be related to the formation of tumour hybrids [ 16 , 124 , 150 158 ]. However, precise regulatory mechanisms to control e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the importance of physiological cell fusion, there is profound scientific consensus that cell-cell fusion events also occur in human cancers and that disease progression can be related to the formation of tumour hybrids [ 16 , 124 , 150 158 ]. However, precise regulatory mechanisms to control e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cells (CTC), discovered a century and a half ago [74], are neoplastic cells present in the blood of patients with solid tumors and are thought to include the precursors of metastases [75]. Paradoxically, a fraction or, in some cases, most of CTC released by some non-hematological tumors, such as melanoma, breast, ovarian, and pancreatic cancers, were found to carry CD45, a protein whose expression is normally restricted to bone-marrow derived cells [30,51,[76][77][78]. Hence, these cells (CTC-CD45) were viewed as a persistent artifact until an appeal to give them a closer look [77] revealed that they indeed exist [79] and that their concentration inversely correlates with the survival of patients with pancreatic cancer [30,51].…”
Section: Puzzling Circulating Tumor Cellsmentioning
confidence: 99%
“…The presence of a lymphocyte protein on the cells of non-hematological tumors prompted a hypothesis that CTC-CD45 are hybrids between tumor cells and leukocytes [79]. As a result, these cells have been reported as macrophage-tumor cell fusions [80], circulating hybrid cells [30], or simply hybrids [78]. However, genomic evidence for the hybrid origin of these cells is still unavailable, leaving open other explanations: that CD45 is present due to aberrant gene expression, which is common in cancer, or that cancer cells acquire this protein through trogocytosis [81], a process that enables the intercellular exchange of membrane proteins [82], or by a similar phenomenon termed vampirization [83].…”
Section: Puzzling Circulating Tumor Cellsmentioning
confidence: 99%
“…Independent of cancer etiology, engorged CAMLs (≥50 µm) have shown clinical utility as a prognostic and predictive biomarker for worse outcomes in breast, non-small-cell lung, esophageal, and pancreatic cancers [36,37,[40][41][42]. Further, the presence of CAMLs and their size association to clinical outcomes have been investigated and independently validated by a number of groups [43][44][45][46][47]. While ≥50 µm CAMLs appear to predict decreased survival across multiple solid-tumor types, there is an unexplained phenomenon in which hyper-engorged CAMLs (≥100 µm) appear to predict multi-organ-site metastatic spread and even poorer survival [40,48].…”
Section: Introductionmentioning
confidence: 99%